Modelling and global predictive control for distributed–driven high–speed trains. (10th March 2014) - Wei, Yongsong; Wu, Jing; Li, Shaoyuan
This paper focuses on the modelling and control problem of a type of the Chinese High–Speed Train. A longitudinal dynamic model for a type of Chinese high–speed train is established based on multi–body spring–mass models, where the couplers connecting adjacent coaches are characterised by linear springs. To guarantee the safe operation of trains under certain velocity requirements, a model predictive controller is proposed to deal with in–train force and driving force constraints. Finally, a numerical simulation is given to demonstrate the effectiveness of the proposed methods.